Evaluating the role of paternal factors in aetiology and prognosis of recurrent pregnancy loss: study protocol for a hospital-based multicentre case–control study and cohort study (REMI III project) - Saskia le Cessie; Nadia du Fossé; Marie-Louise van der Hoorn; Michael Eikmans; Sebastiaan Heidt; Annemarie Mulders; Jan van Lith; Eileen Lashley (BMJ Open, 2019)
Introduction Recurrent pregnancy loss (RPL) is defined as the spontaneous demise of two or more pregnancies before the fetus reaches viability. Despite investigation of multiple known maternal risk factors, in more than 50% of couples, this condition remains unexplained. Studies focusing on paternal factors in RPL are scarce, and therefore, paternal evaluation in RPL is currently very limited. However, regarding single miscarriage, there are multiple publications suggesting a contributive role of paternal factors. In this project, we aim to identify paternal factors associated with RPL and to improve couple-specific prediction of future pregnancy outcomes by developing a prediction model containing both maternal and paternal factors.Methods and analysis In a case–control design, the relation between unexplained RPL and paternal age, lifestyle factors, sperm DNA damage and immunomodulatory factors in peripheral blood and semen will be studied. Prospectively, 135 couples with naturally conceived unexplained RPL (cases) and 135 fertile couples without a history of pregnancy loss (controls) will be included, with collection of paternal blood and semen samples and documentation of clinical and lifestyle characteristics. In addition, 600 couples from both groups will be included retrospectively. To adjust for confounders, multivariate logistic regression will be used. The predictive value of paternal and maternal factors will be studied in the total RPL cohort consisting of approximately 735 couples. The primary outcome of the cohort study is live birth within 5 years after initial visit of the clinic. Secondary outcomes are ongoing pregnancy, time interval until next pregnancy and pregnancy complications.Ethics and dissemination This project is approved by the Medical Research Ethics Committee of the Leiden University Medical Center. No risks or burden are expected from the study. The findings of this study will be disseminated via peer-reviewed publications and presentations at international conferences.Trial registration number NL7762